2022
DOI: 10.1371/journal.pone.0269980
|View full text |Cite
|
Sign up to set email alerts
|

Strategic complements: Poverty-targeted subsidy programs show additive benefits on household toilet purchases in rural Cambodia when coupled with sanitation marketing

Abstract: While poverty-targeted subsidies have shown promise as a means of reducing financial constraints on low-income populations to invest in new latrines, concerns have been raised about whether they may reduce demand for new latrines among non-eligible, non-poor populations, especially in geographically limited or closed markets. Using quasi experimental methods, we investigate the interaction effects of the “CHOBA” subsidy, a partial poverty-targeted monetary incentive to build a toilet, and a sanitation marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This is because probably they could not afford to construct a pit-latrine and other materials associated with CLTS uptake. According to a Cambodian study, it was revealed that provision of subsidy programs in CLTS implementation led to improvement in its uptake among the poorest (Hoo et al, 2022).…”
Section: 68%mentioning
confidence: 99%
“…This is because probably they could not afford to construct a pit-latrine and other materials associated with CLTS uptake. According to a Cambodian study, it was revealed that provision of subsidy programs in CLTS implementation led to improvement in its uptake among the poorest (Hoo et al, 2022).…”
Section: 68%mentioning
confidence: 99%